The Effect of Price Discount, Live Streaming, and Customer Reviews on the Purchase Decisions of Online Customers at Shopee in the Special Region of Yogyakarta - Sujoko Sujoko; Chindy Ariska Amanatun; Hening Nakuloadi (Green Publisher Indonesia, 2026)
This study examines the influence of price discounts, live streaming, and customer reviews on purchasing decisions among Shopee users in the Special Region of Yogyakarta. The rapid growth of e-commerce in Indonesia has intensified competition among online marketplaces, encouraging sellers to adopt various digital marketing strategies to attract consumers. Price discounts, interactive live streaming features, and customer reviews are considered important factors influencing consumer purchasing behavior in online shopping environments. Therefore, this study aims to analyze the partial and simultaneous effects of these variables on purchasing decisions. This research employed a quantitative approach using a survey method. Data were collected through online questionnaires distributed to 123 Shopee users in Yogyakarta selected using purposive sampling techniques. The collected data were analyzed using multiple linear regression analysis with the assistance of SPSS software. Several classical assumption tests, including validity, reliability, normality, and heteroscedasticity tests, were also conducted to ensure data quality. The results showed that price discounts and live streaming have a positive and significant effect on purchasing decisions. Meanwhile, customer reviews have a positive but insignificant effect on purchasing decisions. Simultaneously, the three independent variables significantly influence purchasing decisions among Shopee consumers. In conclusion, digital promotional strategies, especially price discounts and live streaming, play an important role in increasing consumer purchasing decisions in e-commerce platforms.